2019
DOI: 10.1016/j.celrep.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Signals Protein Status to the Brain and Adaptively Regulates Food Choice and Metabolism

Abstract: Highlights d Mice adaptively alter metabolism and food choice during protein restriction d The liver hormone FGF21 is robustly increased by protein restriction d Metabolic responses to protein restriction require FGF21 signaling in the brain d Brain FGF21 also mediates adaptive changes in macronutrient selection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
184
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(208 citation statements)
references
References 70 publications
9
184
4
Order By: Relevance
“…This highlights that a low Thr diet can induce many of the positive effects of dietary AA restriction while avoiding some negative side effects such as lean tissue wasting. On this, similar to that previously shown for dietary protein/AA dilution 14,16,21,49,65 , and SCAA or BCAA restriction 21,38,[42][43][44] , low Thr feeding also retarded development of obesity-induced metabolic dysfunction in a mouse model ( Fig. 5).…”
Section: Discussion (1814 Words)supporting
confidence: 88%
See 1 more Smart Citation
“…This highlights that a low Thr diet can induce many of the positive effects of dietary AA restriction while avoiding some negative side effects such as lean tissue wasting. On this, similar to that previously shown for dietary protein/AA dilution 14,16,21,49,65 , and SCAA or BCAA restriction 21,38,[42][43][44] , low Thr feeding also retarded development of obesity-induced metabolic dysfunction in a mouse model ( Fig. 5).…”
Section: Discussion (1814 Words)supporting
confidence: 88%
“…Several studies have demonstrated that systemic 14,16,24,25,32,40,44,65 or liver-restricted 14,26 Fgf21loss retards the downstream metabolic effects of dietary protein/AA restriction. In particular, these effects are likely to be mediated by central nervous system FGF21 signalling 65 , to stimulate nutrient uptake/oxidation in adipose tissue and heart 14,16 . Here we extend upon these findings and demonstrate that adult, liver-specific FGF21 loss completely abrogates the systemic metabolic remodelling with dietary Thr restriction (Fig.…”
Section: Discussion (1814 Words)mentioning
confidence: 99%
“…These results suggest that in protein restricted animals, 'phasic' bursting activity of dopamine mesolimbic neurons evokes greater dopamine release, relative to control animals. As phasic responses of mesolimbic dopamine neurons are well known to convey important information about primary reinforcers like food and associated stimuli [16,19,23,63,65], an increase in NAc dopamine levels in response to salient events may alter motivated behaviors like food preferences [11,13] and increase the rewarding properties of protein-enriched food in restricted/deprived animals [12]. Interestingly, protein restriction did not alter the phasic/tonic ratio either in NAc or dorsal striatum, suggesting that protein restriction at adulthood may induce a more general increase in capacity of terminals for dopamine release rather than by enhancing the contrast between different dopamine signaling modes [57,66].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of insulin on the dopamine system and dopamine-related behaviors are complex and depend on insulin concentration, brain region, cell type and the current physiological state [71]. Protein restriction is known to increase insulin sensitivity and glucose metabolism [13,72], which may then modulate dopamine's neurobiological and behavioral functions. The interaction of the dopamine and insulin systems in response to different context of protein diet warrants further ex vivo and in vivo investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation